Antiviral Effect of Lithium Chloride on Replication of Marek’s Disease Virus in Chicken Embryonic Fibroblasts - Huifeng He (MDPI AG, 2021)
To investigate the antiviral effect of lithium chloride (LiCl) on the replication of Marek’s disease virus (MDV) in chicken embryonic fibroblast (CEF) cells, real-time PCR, Western blotting, plaque counting, and indirect immunofluorescence experiments were performed at different time points of LiCl treated CEF cells with virus infection. The results demonstrated that LiCl could affect multiple steps of virus replication and inhibit viral gene expression and protein synthesis in a dose- and time-dependent manner. Moreover, LiCl could directly affect viral infectivity as well. In addition, LiCl significantly affected the gene expression of IFN-β related genes in virus-infected cells. These results indicate that LiCl significantly inhibits MDV replication and proliferation in CEF cells and it has the potential to be used as an antiviral agent against MDV.